the effect of using the mpu tantular museum as a social science learning resource on improving student history learning outcomes - Isnaini, Dewi (Jurnal Dialektika Pendidikan IPS, 2022)
Learning in the field of education is usually carried out in the classroom and several times it is not carried out in the classroom according to the subjects being studied. Various available learning resources can be used by teachers to make it easier for students to better master the material in order to obtain maximum learning outcomes. One of them is a Museum. Museums can be used as historical learning materials for education, including elementary, junior and high school education, and history also has an exclusive function. And local learning resources that have the potential to help learning are museums. The purpose of this study was to determine whether the use of the Mpu Tantular Museum as a social studies learning resource would increase students' understanding of historical events. This research uses quantitative techniques and ex-post facto causal research approach. The study was conducted at MTs Darul Huda Srigading Ngoro Mojokerto with a sample of 22 students in class VII-B and 24 students in IX-A. With the independent variable (X) the utilization of the Mpu Tantular Museum and the dependent variable (Y) learning outcomes. Test the validity of the instrument using expert tests by lecturers with research instruments in the form of questionnaires and test questions. Normality and linearity tests are prerequisites for data analysis. By using t-test and simple linear regression analysis, analyze the test results. based on the result Y=47,799 + 0.654X. The use of the Mpu Tantular Museum has a significant effect on student learning outcomes in class VII-B MTs Darul Huda, based on the results of hypothesis testing which shows a significance value of 0.025 <0.05. Of the factors that contribute to the increase in learning outcomes, 22.6 percent are other variables, and the remaining 77.4 percent are other variables.